Effect of cinnamomum zeylanicum blume essential oil on the rowth and morphogenesis of some potentially pathogenic Aspergillus species - Carmo,Egberto Santos (2008)
Cinnamomum zeylanicum Blume is known for a wide range of medicinal properties. This study aimed to assess the interference of C. zeylanicum essential oil on the growth and morphogenesis of some potentially pathogenic Aspergillus species. The essential oil presented strong antifungal effect causing the growth inhibition of the assayed strains and development of large growth inhibition zones. MIC50 and MIC90 values were 40 and 80 µL/mL, respectively. 80, 40 and 20 µL/mL of the oil strongly inhibited the radial mycelial growth of A. niger, A. flavus and A. fumigatus along 14 days. 80 and 40 µL/mL of the oil caused a 100% inhibition of the fungal spore germination. Main morphological changes observed under light microscopy provided by the essential oil in the fungal strains were decreased conidiation, leakage of cytoplasm, loss of pigmentation and disrupted cell structure indicating fungal wall degeneration. It is concluded that C. zeylanicum essential oil could be known as potential antifungal compound, particularly, to protect against the growth of Aspergillus species.